PRIORITIZATION STRATEGIES FOR ENHANCING TOURISM DEVELOPMENT AT PLAOSAN TEMPLE CULTURAL HERITAGE SITE IN KLATEN REGENCY - Sayuti, Sayuti; Sarwani, Sarwani; Sutikno, Achmad Nur (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2024)
This research aims to determine priority strategies for developing Plaosan Temple cultural heritage tourism. The overall resources used in developing Plaosan Temple cultural heritage tourism can be optimized by determining these priority strategy choices. This research uses a qualitative descriptive research design. Data collected using interviews, observation, and documentation was analyzed using the SWOT technique. The results of the calculation of Internal Factors in the form of a combination of Strength (S) and Opportunity (O) factors obtained a weighted value of 0.80, which is the highest value. The combination of Weakness (W) and Threat (T) factors has a weighted value of 0.36. The total score obtained for internal factors and strengths is 2.12, and for weaknesses is 1.16, so the point used on the horizontal axis or x-axis can be determined as 0.96. The total score obtained for external factors and opportunities is 1.82, and threats are 1.50, so the vertical or y-axis point is at 0.32. For this reason, the coordinate point is 0.96; 0.32 lies in Quadrant I as an Aggressive strategy. Alternative strategy options are: Accelerate the formation of National Strategic Areas by utilizing Presidential Regulation No. 18/2020 Strategic Priority Projects (Major Project Priority Tourism Destinations (KSPN-BYP)), and Strategy: Increase promotion by the central government, Klaten Regional Government, and related stakeholders from the community and private sector.Keywords: SWOT Analysis, EFAS, IFAS, Priority Strategy